2022
DOI: 10.3389/fonc.2022.947302
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of combined inflammatory and nutritional biomarkers in HCC within the Milan criteria after hepatectomy

Abstract: AimsThis study aimed to evaluate the predictive value of the combined prognostic nutritional index (PNI) and GGT/ALT for the postoperative prognosis of patients with hepatocellular carcinoma (HCC) within Milan criteria undergoing radical hepatectomy.MethodsThis single-center retrospective study included 283 patients with HCC within the Milan criteria who underwent hepatectomy. The receiver operating characteristic (ROC) curve was used to calculate the optimal PNI and GGT/ALT cut-off values. Pre-treatment PNI, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…On the other hand, other formulas have been developed starting from these inflammatory markers and other serum values, as nutritional indexes. This is the case of the Glasgow prognostic score (GPS) and the modified GPS, calculated from the CRP and the albumin level (47,48), the prognostic nutritional index (PNI) combining lymphocyte count and serum albumin (29,49) or the inflammation-immunitynutrition score (IINS), a combination of CRP, lymphocyte count and serum albumin level (30). All these equations, although not systematically integrated in clinical practice, have been widely described as factors of impaired survival in literature.…”
Section: Serum Inflammatory Markersmentioning
confidence: 99%
“…On the other hand, other formulas have been developed starting from these inflammatory markers and other serum values, as nutritional indexes. This is the case of the Glasgow prognostic score (GPS) and the modified GPS, calculated from the CRP and the albumin level (47,48), the prognostic nutritional index (PNI) combining lymphocyte count and serum albumin (29,49) or the inflammation-immunitynutrition score (IINS), a combination of CRP, lymphocyte count and serum albumin level (30). All these equations, although not systematically integrated in clinical practice, have been widely described as factors of impaired survival in literature.…”
Section: Serum Inflammatory Markersmentioning
confidence: 99%
“…They can indicate the prognosis of patients with various tumors [9][10][11][12][13][14], such as pancreatic cancer, cervical cancer, thyroid cancer, gastric cancer, lung cancer, and esophageal cancer. Of course, it also includes HCC [15][16][17][18][19][20][21]. Not only that but also studies show that these inflammatory markers can help to identify and diagnose tumors at an early stage [22].…”
Section: Introductionmentioning
confidence: 99%
“…Increasing evidence suggests that immune status, as well as inflammatory and nutritional status, affects the prognosis of malignant tumors 16 . It has been shown that inflammation markers, such as systemic immune‐inflammation index (SII), platelet–lymphocyte ratios (PLR), and neutrophil–lymphocyte ratio (NLR), are highly predictive of the outcomes of breast cancer, colorectal cancer, liver cancer, and other cancers 17–19 . The nutritional status of cancer patients also has an impact on the prognosis 20 .…”
Section: Introductionmentioning
confidence: 99%
“… 16 It has been shown that inflammation markers, such as systemic immune‐inflammation index (SII), platelet–lymphocyte ratios (PLR), and neutrophil–lymphocyte ratio (NLR), are highly predictive of the outcomes of breast cancer, colorectal cancer, liver cancer, and other cancers. 17 , 18 , 19 The nutritional status of cancer patients also has an impact on the prognosis. 20 Inflammatory factors and immunity in the body can be reflected more comprehensively by SII, which is a comprehensive index of neutrophil, platelet, and lymphocyte counts.…”
Section: Introductionmentioning
confidence: 99%